Bacterial, fungal and parasitic co-infections in leprosy: A scoping review. - Luis Alberto Ribeiro Fróes; Tereza Setsuko Toma; Marie Jachiet; Laurie Rousset; Rosana Evangelista Poderoso; Maria Angela Bianconcini Trindade (PLoS Neglected Tropical Diseases)
Background In leprosy patients, the most commonly reported non-viral co-infections are Tuberculosis, Leishmaniasis, Chromoblastomycosis and Helminths. The presence of a secondary infection is believed to increase the likelihood of leprosy reactions. The purpose of this review was to describe the clinical and epidemiological characteristics of the most reported bacterial, fungal, and parasitic co-infections in leprosy. Methodology/principal findings Following the PRISMA Extension for Scoping Reviews guidelines, a systematic literature search was conducted by two independent reviewers, resulting in the inclusion of 89 studies. For tuberculosis, a total of 211 cases were identified, with a median age of 36 years and male predominance (82%). Leprosy was the initial infection in 89% of cases, 82% of individuals had multibacillary disease, and 17% developed leprosy reactions. For leishmaniasis, 464 cases were identified, with a median age of 44 years and male predominance (83%). Leprosy was the initial infection in 44% of cases, 76% of individuals presented with multibacillary disease, and 18% developed leprosy reactions. Regarding chromoblastomycosis, we identified 19 cases with a median age of 54 years and male predominance (88%). Leprosy was the primary infection in 66% of cases, 70% of individuals had multibacillary disease, and 35% developed leprosy reactions. Additionally, we found 151 cases of co-infection with leprosy and helminths, with a median age of 43 years and male predominance (68%). Leprosy was the primary infection in 66% of cases, and 76% of individuals presented with multibacillary disease, while the occurrence of leprosy reactions varied from 37% to 81% across studies. Conclusion We observed a male-dominated pattern of co-infections among working-age individuals with multibacillary leprosy. Unlike prior studies reporting increased leprosy reactions in chronic viral co-infections, our findings did not indicate any increase among bacterial, fungal, or parasitic co-infections. Rather, co-infections with tuberculosis and leishmaniasis appeared to reduce leprosy reactions.